Claused Used In Testimonials Duolingo Application: Systemic Functional Linguistics Analysis - Aurora Horinza; diana rozelin; chandri febri santi (English Language, Linguistics, Literature, And Education Journal, 2020)
The aims of this research are: (1) to find out the types of mood in testimonials Duolingo app, (2) to know the structure mood in testimonials Duolingo app, (3) to find out the types of topical theme in testimonials Duolingo app. In this research, the writer applies the theory of Systemic Functional Linguistics by M. K. Halliday. This research is qualitative research that focused on qualitative research by Creswell in and uses descriptive method by Denzin and Lincoln. The writer used documentation technique for collecting data. The writer used content analysis for technique of analysis. The writer found on the research that: First, there are three types of mood that found in testimonial Duolingo app, which are: Declarative Mood, Imperative Mood and Interrogative Mood. Second, the structure of Mood are the clause that found indicates as the form of Mood element and Residue Element. Third, the writer found two the types of topical theme in testimonial Duolingo app, which are: Unmarked Topical and Marked Topical, Marked topical theme is mostly appear in testimonial Duolingo app.